Chan‐Lam‐type Azidation and One‐Pot CuAAC under CuI‐Zeolite Catalysis. Issue 7 (25th February 2020) - Clerc, Arnaud; Bénéteau, Valérie; Pale, Patrick; Chassaing, Stefan
Abstract: The copper(I)‐exchanged zeolite Cu I ‐USY proved to efficiently catalyze the direct azidation of arylboronic acids with sodium azide under simple and practical conditions, namely at room temperature under air with methanol as solvent and without any additive. This easy‐to‐prepare and cheap catalytic material has been demonstrated to be recyclable and the mild azidation conditions further showed good functional‐group tolerance, leading to a variety of substituted (hetero)aryl azides (18 examples). Interestingly, the azidation reaction has been successfully coupled to a CuAAC reaction, thus allowing access to triazoles from arylboronic acids via a one‐pot Cu I ‐catalyzed process. Abstract : Super fine : Zeolites as nanoreactors for green & fine chemistry – one‐pot route to azides & triazoles from boronic acids